Feasibility of Cage Culture on Lake Malawi, Part 1: Physical, Chemical and Biological Processes - Kaunda, E; Salima, C.; Macuine, M. A.; Msiska, O. V. (European Journal of Applied Sciences, 2024)
The feasibility of cage culture in Malawi was fully evaluated using standard procedures involving a sub-model of dissolved oxygen and phosphorus budget models to compute carrying capacities in relation to bathymetric features. The central lakeshore district of Salima was used as a proxy for other parts of Lake Malawi. The values of carrying capacity varied from 4-5 tons for small cages (5 m diameter by 3 m depth) to 14-17 tons for large cages (10 m diameter x 6 m depth); this compares favorably with 18-22 tones from cages of 12 m diameter x 8 m depth produced by MALDECO Ltd. One site, Sani Maganga was found to be unsuitable because of an inverse relationship between dissolved oxygen and the water depth. On the other hand, values of 61-67 tons for medium cages and 79-86 tones for large cages, respectively, were computed using the phosphorus model, suggesting that this method may be inappropriate for Lake Malawi in its current form. The close correlation between actual and computed values in the dissolved oxygen model demonstrates its relevance. In future, dissolved oxygen should be measured at several depths with water temperature to determine oxygen saturation which is important to fish feed utilization. The phosphorus model needs to be fine-tuned, since it was derived on Trout fish farm modeling in temperate waters; water temperature/oxygen saturation and metabolic rates may be sources of variation. The recommended threshold of 70 ugL-1for phosphorus concentration could still be used. Unsuitable conditions at San Maganga, show that conditions vary from site to site and detailed studies are necessary. Therefore, current findings are not safe to generalize for the whole Lake Malawi.